THE PHENOMENON OF PROCRASTINATION AND PERSPECTIVE OF THIS PROBLEM SOLVING AT UNIVERSITY IN THE CONTEXT OF THE DROPOUT RISK - Katane, Irēna; Jerkunkova, Aleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
One of the problems that needs to be solved in the modern education is the students' procrastination phenomenon. Procrastination is one of the main studying influence factors which results in students delaying learning, obtaining academic debts and being exposed to dropout risk before reaching their career goals. There is a close correlation between students' procrastination and dropout phenomena because as a result of procrastination, students are unable to plan its own time and efficiently self-manage its activities in today's higher education environment. Therefore the aim of the study was to substantiate the phenomenon of academic procrastination in the higher education environment theoretically by outlining the problem solving perspective. The used research methods were theoretical analysis and evaluation of scientific literature as well as reflection of experience. The results of the study prove that academic procrastination is: 1) avoiding various types of study work that is often limited in time, postponing various types of activities to a later, often indefinite period; 2) avoiding decision-making and the consequences of one’s actions and 3) avoiding responsibility. Academic procrastination is a kind of defense mechanism that is triggered by different types of inner personality factors. In order to decrease the influence of procrastination that it leaves on studies and career goals, within career development guidance in university, students should be helped to cognize themselves by self-evaluating their level of procrastination using one of the scientific and recognized methods for evaluating the procrastination level. The academic and research experience of the authors allows to conclude that by providing career development guidance to students, it is possible not only to solve the procrastination problem, but at the same time to prevent the risk of dropping out as well.